RAFAEL MONEO - Escritos sobre arquitectos españoles (1961- 2021) - Monteys, Xavier (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2023)
Rafael MoneoEscritos sobre arquitectos españoles (1961-2021)Madrid: Ministerio de Fomento, 2022. 544 pp. Softcover. Language: Spanish. 20,00 €ISBN. 978-84-498-1082-4